Role of Forensic Osteolgy in positive identification for Forensic investigations to solve medicolgal cases in Punjab, Pakistan - Khadeeja Khan, Muhammad Faisal Aslam, Nadir Ali, Javeria Ghafoor, Muhammad Immran (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Positive identification of human skeletal remains is prime importance to solve the medicolegal cases in unidentified dead bodies. In case of mass disasters, genocide, mass graves, manslaughter and other medicolegal cases, the skeletal data provides enough information to solve the question of identification of the deceased human beings to provide justice even many years after their death. Aim: To see evidentiary value of skeletal data to determine the positive identification by using race ,age sex, stature and other parameters of identification in medicolagal cases of human skeletal remains in medicolegal forensic investigations in Punjab from 2015 to 2022. Study design: In this retrospective study 100 medico-legal cases where positive identification was done from skeletal remains in different medico-legal work performing Forensic departments of Punjab, were analyzed. Methods: In this retrospective study 100 medico-legal cases where positive identification was done from skeletal remains. This skeletal data was collected from different medico-legal cases where the identification was done on bones from five district of Punjab. This data was collected from the District Head Quarter hospitals of these cities from their medico-legal offices to conduct this research study. All the information collected were interred in predesigned Performa before analyzing the data. Descriptive statistics was implied on all the medico-legal cases for data collections and analysis of skeletal data from different bones recovered from the crime-scenes in this research study. Furthermore, standard deviation, F-statistics, and Chi test p-value were also applied to see the association of these parameters of identification with different skeletal remains with highest probability of positive identification from different bones. Results: Forensic anthropological data (skeletal data) was found very high probability to solve the medicolagal cases of forensic investigations to solve the issue of identification of the victims of crimes and mass disaster. Skull bone had high percentage of accuracy (92%) to provide positive identification of race whileage and Sex was a little less (82%). Hip bones alone and with whole pelvic girdle had very high percentage in determining sex with 96% accuracy. Appendicular skeletal (limbs) data had provided very significant (92%) to solve the stature, age and sex for positive identification (90%). Axial skeletal data provided good percentage of Identification (82%) for stature as a parameter of identification in all the medico-legal cases analyzed. Conclusion: Forensic investigations without skeletal data found incomplete to provide positive identification of victims of violent crimes and mass disasters. Skull bone was found very important for positive identification of victims especially identifying race and age , the parameters of identification. Pelvic bone and whole bony pelvis provided the best identification for sex as a parameter of identification. Axial and appendicular skeletal data demonstrated good accuracy for stature estimation for the purpose of identification of skeletal remains. Many social and demographic factors play their role for the prevalence of medico-legal cases where the perpetrators of crime dismember or skeletonise the dead body to hide their identification. By the virtue of research and modern sciences all skeletal remains are identified and brought to justice in medico-legal system. Keywords: Osteology, Forensic anthropology, skeletal data, positive identification.